Monday

July 28, 2014

July 28, 2014

Posted by **Dajah** on Sunday, January 9, 2011 at 6:53pm.

- Algebra II -
**Marth**, Sunday, January 9, 2011 at 6:55pmx^2+2x-3 factors into (x+3)(x-1). You can divide x^4-5x^3-16x^2+23x-3 by (x+3) and (x-1) using synthetic division, which may be easier.

**Related Questions**

Algebra - There are two solutions to | 16x - 5 | = 3. The greatest solution is ...

algebra - Solve the system by addition or substitution. 16x-4y=20 y=4x-4 I ask ...

Algebra - almost done with Algebra...help! 2 3x – 6(2x – 0.055) = 10x + 0.515 I ...

algebra - x^2 +16x+64 x^2+16x=64 (x=3)^2=16x-64 16x=-64 x=-4 Check this problem ...

algebra - Perform the division, x squared + 16x +63 divided by x + 7

Math - A few here. 4x-8 ------ x(squared)-4 _________________________ 2m(squared...

Discrete Math - Please help with this problem. Thanks a/ Show that for any real ...

Math (Algebra II) - I'm trying to finish up my summer math packet, and I'm ...

Math - 5(-3x - 2) - (x - 3) = -4(4x + 5) + 13 Answer Multiply factors. -15x - 10...

Algebra II - Simplify: 4xy^3/z^2 divided by (8x^2y/z^3)^2 I came up with the ...